Regulating bile acids signaling for NAFLD: molecular insights and novel therapeutic interventions - Wei, Meilin; Tu, Wei; Huang, Genhua (Frontiers in Microbiology, 2024)
Nonalcoholic fatty liver disease (NAFLD) emerges as the most predominant cause of liver disease, tightly linked to metabolic dysfunction. Bile acids (BAs), initially synthesized from cholesterol in the liver, undergo further metabolism by gut bacteria. Increasingly acknowledged as critical modulators of metabolic processes, BAs have been implicated as important signaling molecules. In this review, we will focus on the mechanism of BAs signaling involved in glucose homeostasis, lipid metabolism, energy expenditure, and immune regulation and summarize their roles in the pathogenesis of NAFLD. Furthermore, gut microbiota dysbiosis plays a key role in the development of NAFLD, and the interactions between BAs and intestinal microbiota is elucidated. In addition, we also discuss potential therapeutic strategies for NAFLD, including drugs targeting BA receptors, modulation of intestinal microbiota, and metabolic surgery.